Bending Analysis of Steel-Concrete Composite Beams with Porosity - Kumar, Prashant; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
This study investigated the bending behavior of a simply supported pervious composite beam using the finite element method based on cubic order beam theory. The cubic order axial displacement was assumed and solved using shear stress-free conditions on the extreme surfaces of the composite beam. For simplicity, this study considered one-dimensional axial displacement. Three nodded finite elements were assumed, and each node had eight unknowns. Shear locking was eliminated in the present model by numerical integration of the stiffness matrix. A uniform porosity distribution was implemented in the upper layer of the composite beam. The damping ratio was also considered for the bending analysis. The accuracy of the present model makes it robust for the analysis of composite beams.